In Vivo Biocompatibility and Biodegradation Test of Two Barrier Membranes for Guided Tissue Regeneration - Machiavelli Clavesia; Stephani Dwiyanti; Veronika Maria Sidharta; Dyonesia Ary Harjanti; Mora Octavia; Eko Adi Prasetyanto; Tena Djuartina
This study evaluates biocompatibility and biodegradation properties of PCL/Chitosan/BG-NP/Tetracycline and compares them with commercially available Sure-Derm membrane in Sprague Dawley Rats. Two different membranes (PCL/Chitosan/BG-NP/Tetracycline membrane and SureDerm membrane) were randomly inserted into subcutaneous pouches in the backs of 54 Sprague Dawley rats. The animals were sacrificed at day 7, 21, and 63. Biocompatibility properties (number and distribution of inflammatory cells, necrosis, neovascularisation, fibrosis, fatty infiltrate, tissue integration, tissue ingrowth) was assessed according to DIN EN ISO 10993-6. Biodegradation property was assessed macroscopically to check for membrane degradation rate. In terms of biocompatibility properties, the test membrane had overall irritancy score of 0 at day 7 and 21, and 0.66 at day 63, and it is considered non-irritant. Biodegradation of test membrane is faster compared to SureDerm at day 7 and 21. However, there is no significant difference between the two membranes at day 63. The GTR membrane PCL/Chitosan/BG-NP/Tetracycline is a good membrane with comparable biocompatibility and biodegradation properties to the SureDerm membrane.